Mechanical behaviour of natural fibre reinforced thermoplastic braided composite rods - Parveen, Shama (2012)
In the present work, braided composite rods (BCRs) have been developed through braiding of polypropylene (PP) fibres around an axially oriented core, made of a mixture of PP and sisal fibres and subsequent consolidation of the produced structures under heat and pressure. Tensile properties of these BCRs were characterized. The effect of alkali treatment of sisal fibres on their surface morphology as well as mechanical properties of sisal fibres and produced BCRs was thoroughly investigated. It was observed that the tensile properties of developed BCRs improved strongly with the increase in sisal fibre vol.% and moreover, the alkali treatment improved the tensile properties of sisal fibre and their interfacial interactions with PP matrix, leading to enhanced tensile behaviour of BCRs.